Temporal and propositional de se: evidence from Romanian subjunctive mood - Brasoveanu, Adrian (ZAS Papers in Linguistics, 2006)
The paper investigates the interpretation of the Romanian subjunctive B (subjB) mood when it is embedded under the propositional attitude verb crede (believe). SubjB is analyzed as a single package of three distinct presuppositions: temporal de se, dissociation and propositional de se. I show that subjB is the temporal analogue of null PRO in the individual domain: it allows only for a de se reading. Dissociation enables us to show that subjB always takes scope over a negation embedded in a belief report. Propositional de se derives this empirical generalization. The introduction of centered propositions (generalizing centered worlds), together with propositional de se, dissociation and the belief 'introspection' principles, derives the fact that subjB belief reports (unlike their indicative counterparts) are infelicitous with embedded probabil.